The effect of a counseling program to improving psychological alert and stopping the ball by diving among futsal goalkeepers - Aseel Naji Fahd; Noor Hatem AlHaddad; Ali Radhi Abdul Hussein; Aseel Ali (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Psychology is a science closely related to many sports, whether team sports like football or individual sports. Counseling psychology is an applied branch of psychology that seeks to enhance and develop positive behavior and psychological characteristics in individuals. Psychological mobilization is an important concept that counseling psychology focuses on to enhance it in athletes.